Comparing skeletal development of wild and hatchery-reared Senegalese sole (Solea senegalensis, Kaup 1858): Evaluation in larval and postlarval stages - Gavaia, Paulo J. (2014)
The Senegalese sole is a marine pleuronectiform that naturally occurs in Southern Europe and Mediterranean region where it is being produced in aquaculture, in particular in Portugal and Spain. The aim of this study was to assess the quality of hatchery-reared larvae in comparison with those reared in the wild, and determine to which extension wild growing larvae are also affected by skeletal deformities. The main structures affected included those forming the axial skeleton, the caudal fin complex and both anal and dorsal fins, with the most prevalent anomalies affecting caudal vertebrae and arches. Hatchery-reared fish presented a higher incidence of deformities (79%) compared with the 19% observed in wild specimens. In wild postlarvae collected in Autumn no deformities were observed. This work clearly shows that wild Senegalese sole present less skeletal deformities than those hatchery-reared during larval stages, indicating a selective mortality of wild deformed fish and/or an effect of aquaculture-related rearing conditions in the development of skeletal deformities in sole.